EVALUASI USABILITY WEBSITE DINAS PERPUSTAKAAN DAN KEARSIPAN PROVINSI BENGKULU BERDASARKAN PERSEPSI PENGGUNA - Hanif Fathin Siddiq; Marwan Arwani; Fransiska Timoria Samosir (Perpustakaan Nasional RI, 2020)
Purpose. The purpose of this research is to find out the usability of Library and Archive Department of Bengkulu Province website. Method. The research used a descriptive method with a quantitative approach by distributing questionnaires to 100 visitors of Library and Archive Department. Accidental sampling was used as the sampling technique. The data was then analyzed and presented in tabular form. Results and discussion. The results of this research showed that the website usability on the component of convenience obtained an average score of 3.9 (three point nine) points and is categorized ‘very good’, the component of efficiency obtained an average score of 3.6 (three point six) points and is categorized ‘good’, the component of memorability obtained an average score of 3.7 (three point seven) points and is categorized ‘good’, the component of error obtained an average score of 2.5 (two point five) points and is categorized ‘bad’, and the component of satisfaction obtained an average of 3.7 (three point seven) points and is categorized ‘good’. Based on the recapitulation, the average value for all components obtained 3.6 (three point six) points, which is categorized ‘good’. Therefore, the usability of Library and Archive Department of Bengkulu Province website based on user’s perception is good, which means the website is easy to use by users, efficient for finding information, easy to remember, and its link, layout menu and facilities have met the user’s satisfaction.points